BRAKEMEIER, Gottfried. Sabedorias da fé num mundo confuso. São Leopoldo: Sinodal, 2014. 149 p. - Renato Westphal, Euler (Vox Scripturae - Revista Teológica Internacional, 2014)
BRAKEMEIER, Gottfried. Sabedorias da fé num mundo confuso. São Leopoldo: Sinodal, 2014. 149 p.